Heterogeneously catalyzed epimerization of menthol stereoisomers - An instructive example to account for diffusion limitations in complex reaction networks - Etzold, Bastian; Jess, Andreas (Chemical Engineering & Technology, 2008)
The heterogeneously catalyzed epimerization of menthol stereoisomers is an important step in the synthesis of (-)-menthol by the Haarmann and Reimer process. For an accurate design of a technical reactor, the intrinsic kinetics as well as pore diffusion limitations have to be taken into account. The epimerization consists of a complex reaction network and so a simple approach using effectiveness factors based on Thiele moduli is not possible. In this work, a method is presented to simultaneously calculate the change in concentrations in the bulk phase as well as within the porous particles with time (fixed bed reactor) or local position (batch reactor). A commercially available numerical software was used to solve the differential equations. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
Created from Fastlane, Scopus look-up
Keywords: Epimerization; Mass transfer; Menthol; Pore diffusion